2015
DOI: 10.1016/j.vetmic.2015.05.020
|View full text |Cite|
|
Sign up to set email alerts
|

Characterisation of a mobilisable plasmid conferring florfenicol and chloramphenicol resistance in Actinobacillus pleuropneumoniae

Abstract: HighlightsFirst complete sequence of a floR plasmid from Actinobacillus pleuropneumoniaeExtended similarity to floR plasmids in other Pasteurellaceae speciesConjugal transfer between between species confirmed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…FloR codes for a membrane-associated exporter protein that promotes the efflux of florfenicol and chloramphenicol from the bacterial cell. To date, this resistance gene has only been found in plasmids of various bacteria: E. coli (Cloeckaert et al, 2000), Mannheimia haemolytica (Katsuda et al, 2012), and Actinobacillus pleuropneumoniae (Bossé et al, 2015). Therefore, the presence of catAIII and the lack of plasmids might explain the phenicol resistance phenotype of Pm238.…”
Section: Resultsmentioning
confidence: 99%
“…FloR codes for a membrane-associated exporter protein that promotes the efflux of florfenicol and chloramphenicol from the bacterial cell. To date, this resistance gene has only been found in plasmids of various bacteria: E. coli (Cloeckaert et al, 2000), Mannheimia haemolytica (Katsuda et al, 2012), and Actinobacillus pleuropneumoniae (Bossé et al, 2015). Therefore, the presence of catAIII and the lack of plasmids might explain the phenicol resistance phenotype of Pm238.…”
Section: Resultsmentioning
confidence: 99%
“…Iron metabolism is of high importance for the pathogen to survive and multiply in the host. It has been shown recently that catecholamine binding to App facilitates iron uptake, although iron availability is highly decreased during acute infection as a physiological acute reaction during inflammation (Humann-Ziehank et al, 2014;Li et al, 2015). The fact that more than 50 App genes are involved in iron uptake and metabolism (Xu et al, 2008), some of which are differentially expressed during infection Klitgaard, Friis, Jensen, Angen, & Boye, 2012), supports the major importance of this bacterial adaptation strategy for disease pathogenesis (Boss e et al, 2002).…”
Section: Experimental Dual Infections With Swine Influenza Virus (Sivmentioning
confidence: 99%
“…Recently, plasmids conferring resistance to florfenicol and chloramphenicol were isolated from App clinical isolates from Greece and Brazil (Bossé et al., ; Cunha da Silva et al., ), and enrofloxacin‐resistant strains have been reported in Taiwan and the UK (Bossé, Li, Rogers, et al., ; Wang et al., ). It has been demonstrated that whole‐genome sequencing can be used as predictor for App resistance to antimicrobial substances (Bossé, Li, Rogers, et al., ).…”
Section: Prevention Control and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As we all know, the antibacterial efficiency depends on the susceptibility and exposure level of pathogens to antimicrobial agents. The latest antimicrobial susceptibility testing showed that (i) most of serotypes of App were still susceptible to FF, except a serotype 2 isolate named MIDG3446, and (ii) the determined MICs of FF for App MIDG2331DureC::nadV (serotype 8 clinical isolates) and App MIDG3446 were 2 and 8 lg/mL, respectively (Boss e et al, 2014;Boss e et al, 2015). When the pigs received a single dose of FF at 20 mg/kg via intramuscular injection, the averaged C max was less than the MIC for App MIDG3446, but 2.44 times higher than the MIC for App MIDG2331DureC::nadV; the time that FF concentration in lung interstitial fluid exceeded the MIC (T >MIC ) was approximately 6 h for App MIDG2331DureC::nadV.…”
Section: Discussionmentioning
confidence: 99%